Exploring public attitudes toward live-streaming fitness in China: A sentiment and content analysis of China's social media Weibo - Tian, Rui; Yin, Ruheng; Gan, Feng (Frontiers in Public Health, 2022)
Objectives Live-streaming fitness is perceived by the Chinese government as an invaluable means to reduce the prevalence of physical inactivity amid the COVID-19 pandemic. This study aims to investigate the public altitudes of the Chinese people toward live-streaming fitness and provide future health communication strategies on the public promotion of live-streaming fitness accordingly. Methods This study collected live-streaming fitness-related microblog posts from July 2021 to June 2022 in Weibo, the Chinese equivalent to Twitter. We used the BiLSTM-CNN model to carry out the sentiment analysis, and the structured topic modeling (STM) method to conduct content analysis. Results This study extracted 114,397 live-streaming fitness-related Weibo posts. Over 80% of the Weibo posts were positive during the period of the study, and over 85% were positive in half of the period. This study finds 8 topics through content analysis, which are fitness during quarantine; cost reduction; online community; celebrity effect; Industry; fitness injuries; live commerce and Zero Covid strategy. Conclusions It is discovered that the public attitudes toward live-streaming fitness were largely positive. Topics related to celebrity effect (5–11%), fitness injuries (8–16%), live commerce (5–9%) and Zero Covid strategy (16–26%) showed upward trends in negative views of the Chinese people. Specific health communication strategy suggestions are given to target each of the negative topics.